Dampak Virus Terhadap Kota dalam Cerpen Amarah Virus Pada Negeriku Karya Ike Loveni Nur Safitri - Winda Laura Yogi; Wa Ode Adzika Nurul Fatiha; Eva Dwi Kurniawan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This research aims to analyze the content of the short story entitled "Amarah Virus Pada Negeriku" by Ike Loveni Nur Safitri based on the impact of the virus on city conditions from economic, population aspects in the form of migration and transportation. The research approach used in this research is descriptive qualitative with a content analysis strategy method. This short story tells about the rapid increase in the Covid-19 virus and the policies implemented by the government to suppress its spread. From this, the impact on city conditions emerged, such as the economy in the city being disrupted, transportation within the city not running well, the migration process being disrupted, and the policies implemented apparently helping to reduce problems in the city, especially air pollution.